The Gambia : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This Joint Staff Advisory Note discusses the Poverty Reduction Strategy Paper (PRSP) for The Gambia. The Gambian authorities have prepared their second PRSP covering the years 2007 to 2011. The PRSP supports greater decentralization and expansion of social development funds to better target public services for the poor. Given that there has been limited progress in implementing the Local Government Act in 2002, the IMF staff recommends the preparation of a country-owned implementation plan and a sensitization program that would create momentum.